2017
DOI: 10.12659/msm.899646
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 6-chloro-N-[3,4-disubstituted-1,3-thiazol-2(3H)-ylidene]-1,3-benzothiazol-2-amine Using Drug Design Concept for Their Targeted Activity Against Colon Cancer Cell Lines HCT-116, HCT15, and HT29

Abstract: BackgroundColorectal adenocarcinoma is the second leading cause of cancer-related death in the world. The stage of the disease is related to the survival of the patient, and in early phases surgery is the main modality of treatment. The main aim of modern medicinal chemistry is to synthesize small molecules via drug designing, especially by targeting tumor cells.Material/MethodsA new series of 19 compounds containing benzothiazole and thiazole were designed. Molecular docking studies were performed on the desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…In both pyrazolo[1,5-c] quinazolin-2-one (class A) and 2-methylquinazolin-4(3H)-one (class B) derivatives, chloro-substituted molecules (compounds IXa and XIIIa) were found to fit better in the active site of the receptor than those with nitro substituents (compounds IXb and XIIIb). This is consistent with previously reported results that halogen derivatives mostly fit better in the active site of the EGFR enzyme ( 32 ).…”
Section: Discussionsupporting
confidence: 94%
“…In both pyrazolo[1,5-c] quinazolin-2-one (class A) and 2-methylquinazolin-4(3H)-one (class B) derivatives, chloro-substituted molecules (compounds IXa and XIIIa) were found to fit better in the active site of the receptor than those with nitro substituents (compounds IXb and XIIIb). This is consistent with previously reported results that halogen derivatives mostly fit better in the active site of the EGFR enzyme ( 32 ).…”
Section: Discussionsupporting
confidence: 94%
“…These results come after the good electronegativity profile due to the chloro substitution which strengthens bonds to the receptor. A study of the structure-activity relationship (SAR) showed the ligand better biological activity by electron-withdrawing group substitution for they can improve the lipophilicity and hydrogen interaction to the receptor ( 16 ). The chloro group also took part in the hydrogen bonds formation and contributed to the bond strengthening, even ranked better than clorobiocin and tetracycline as standards ( 17 ).…”
Section: Discussionmentioning
confidence: 99%